2014
DOI: 10.1097/mpg.0000000000000223
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin and Obestatin Levels in Children With Failure to Thrive and Obesity

Abstract: Compared with the levels in age-matched controls, fasting ghrelin and obestatin levels did not differ significantly in children with FTT. In the children with obesity, the decreased ghrelin and increased obestatin levels suggest a possible adaptive process to positive energy balance. Ghrelin had pronounced age-related changes, and obestatin was associated with the weight status. This may suggest that these 2 hormones use different mechanisms to regulate energy balance and weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 34 publications
2
12
0
2
Order By: Relevance
“…The ghrelin concentration was lowest in obese patients with hypertension, which shows its negative correlation with obesity and obesity-related hypertension. This is in agreement with the results of previously published studies, proving a compensatory decrease in ghrelin when adipose tissue increases [14,24]. However, some previous studies in children found no correlation between ghrelin and obesity-related hypertension, a correlation that was recently shown in adults [15,25].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The ghrelin concentration was lowest in obese patients with hypertension, which shows its negative correlation with obesity and obesity-related hypertension. This is in agreement with the results of previously published studies, proving a compensatory decrease in ghrelin when adipose tissue increases [14,24]. However, some previous studies in children found no correlation between ghrelin and obesity-related hypertension, a correlation that was recently shown in adults [15,25].…”
Section: Discussionsupporting
confidence: 93%
“…Subgroup analysis of included patients revealed a moderate negative statistical correlation between ghrelin/adiponectin and a positive correlation between leptin and anthropometrical parameters in the group of obese children and adolescents with hypertension. These results show their good potential for assessing obesity, which was also confirmed by other studies [24,31]. In the present study, their observed correlation with systolic blood pressure indicates their role in hypertension risk.…”
Section: Discussionsupporting
confidence: 91%
“…Many studies confirmed that sustained hyperglycemia, indicated by elevated HbA1c, is an independent risk factor for the cognitive impairment [39]. Other researchers also noticed that ghrelin levels in obesity patients was lower compared to agematched controls health people [40], and they are negatively correlated with BMI [9,41].…”
Section: Discussionmentioning
confidence: 67%
“…Similarly, studies by Mohsen et al and Wali et al have shown nearly 100 times variability in mean total Ghrelin levels despite using ELISA for the assay. 11,18 All these studies have estimated Ghrelin in the morning hours in fasting state, except in study by Tannenbaum et al where blood sample was taken between 0900 to 1200 hours without consideration to meal time. 17 Present study has shown even more marked difference (nearly 100-1000 times higher) in Ghrelin levels of healthy controls and PEM when compared to above studies.…”
Section: Discussionmentioning
confidence: 99%